Association of soluble ST2, M235T polymorphism of ATG with insulin resistance in diabetic patients with heart failure with preserved ejection fraction. (14th October 2021) - Medentseva, O; Rudyk, I.S; Ovrakh, T.G; Gasanov, I.C; Babichev, D.P; Bondar, T.N
Abstract: Background: It has been shown that the level of the soluble form of suppression of tumorigenicity 2 (sST2) is associated with an unfavorable course of heart failure (HF). On other hand, has been shown a strong influence of ATG polymorphism on HF development. However, the association of M235T polymorphism of ATG and sST2 level with insulin resistance in diabetic patients with HF with preserved ejection fraction (HFpEF) is still unknown. Purpose: To investigate the association between sST2, different types of M235T polymorphism of ATG and insulin resistance in patients with HFpEF and T2DM. Methods: A total of eighty-one patients (49 females and 32 males; mean age 62, 5±7, 3 years) with HFpEF and type 2 diabetes mellitus (T2DM) were examined. Twenty patients had MM genotype, 38 patients had MT genotype and 23 had TT genotype of M235T polymorphism of ATG, which was determined by using of polymerase chain reaction. sST2 was determined by using kits of reagents "PresageST2" (USA). The mean value of sST2 was determined, patients were divided according to the mean. The HOMA-IR was calculated to determine insulin resistance. All statistical tests were 2-tailed and performed in Statistica 10.0, p<0.05 was considered statistically significant. Results: In the group of HFpEF and T2DM with sST2>24.4 ng/ml the HOMA-IR was significantly higher than in the group with sST2<24.4 ng/ml and was 16.24±1.22 and 9.30±1.30, respectively (p<0.05). The HOMA-IR was higher in the TT genotype group compared with carriers of M allele. (p<0.05) (Table 1). Conclusion: High circulating level of sST2 and TT genotype of the M235T polymorphism of the ATG presence was associated with increased insulin resistance in patients with HFpEF and T2DM. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): government funding